Empowering Agribusiness: Crowdfunding as a Catalyst for Young Agri-Entrepreneurs in Malaysia - Nurul Shafika Zul Razali; Selvakkumar K N Vaiappur; Noor Zubaidah Abdul Rahman; Aroop Mukherjee (Information Management and Business Review, 2024)
This study investigates the determinants of crowdfunding adoption among young agribusiness entrepreneurs in Malaysia, particularly those aged 18 to 40. As an alternative to conventional financing options, crowdfunding offers an accessible funding mechanism for entrepreneurs who face challenges securing traditional loans due to limited collateral, high risk, and stringent banking requirements. The study identifies and examines five key factors influencing crowdfunding participation: trust issues, limited financial resources, entrepreneurial attitudes, banking constraints, and awareness of crowdfunding. Data were collected through a survey of 117 young agribusiness entrepreneurs and analyzed using descriptive statistics, Exploratory Factor Analysis (EFA), and Pearson correlation analysis. Results indicate that while crowdfunding awareness positively correlates with the desire to participate, significant barriers persist in terms of trust and financial limitations. These findings contribute to the growing body of knowledge on alternative financing in Malaysia's agricultural sector, providing actionable insights for policymakers and practitioners. The study concludes that targeted interventions are necessary to build trust, improve financial literacy, and promote crowdfunding as a viable tool for economic development within the agribusiness sector.